Rankings and Global Knowledge Governance Higher Education, Innovation and Competitiveness - Erkkilä, Tero (Palgrave Studies in Global Higher Education,, 2018)
Higher education and innovation policies are today seen as central elements in national economic competitiveness, increasingly measured by global rankings. The book analyses the evolution of indicator-based global knowledge governance, where various national attributes have been evaluated under international comparative assessment. Reflecting this general trend, the Shanghai ranking, first published in 2003, has pressured governments and universities all over the world to improve their performance in global competition. More recently, as global rankings have met criticism for their methodology and scope, measurements of various sizes and shapes have proliferated: some celebrating novel methodological solutions, others breaking new conceptual grounds. This book takes a fresh look at developments in the field of knowledge governance by showing how emerging indicators, innovation indexes and subnational comparisons are woven into the existing fabric of measurements that govern our ideas of higher education, innovation and competitiveness. This book argues that while rankings are becoming more numerous and fragmented, the new knowledge products, nevertheless, tend to reproduce ideas and practices existing in the field of global measurement.